2013
DOI: 10.1111/sji.12046
|View full text |Cite|
|
Sign up to set email alerts
|

Different Glycosylation Pattern of Human IgG1 and IgG3 Antibodies Isolated from Transiently as well as Permanently Transfected Cell Lines

Abstract: The effector functions of IgG depend on the presence of carbohydrates attached to asparagine 297 in the Fc-portion. In this report, glycosylation profiles of recombinant wild-type and mutant IgG1 and IgG3 antibodies produced from three cell lines were analysed using LC-ESI-Orbitrap. Clear differences were detected between IgG1 and IgG3 glycoforms, where IgG1 generally contained fucosylated glycoforms, whilst IgG3 mainly were non-fucosylated. When using NS-0 and J558L cells for permanent transfection, IgG1 wt g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…This might be due to the oligomannosidic carbohydrate structure at GS4 (Asn402) which is important for the C1q binding and complementdependent cytolysis [7,35]. In contrast to previous observations [7,33,35], we did not observe differences in effective C1q binding due to glycosylation variations. However, sensitivity of the assay may not allow determining minor differences of activation, as an active fraction of pentamers may be sufficient to provoke a high signal and therefore complement activation did not reveal expression host dependency.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might be due to the oligomannosidic carbohydrate structure at GS4 (Asn402) which is important for the C1q binding and complementdependent cytolysis [7,35]. In contrast to previous observations [7,33,35], we did not observe differences in effective C1q binding due to glycosylation variations. However, sensitivity of the assay may not allow determining minor differences of activation, as an active fraction of pentamers may be sufficient to provoke a high signal and therefore complement activation did not reveal expression host dependency.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences could result from different expression levels of enzymes participating in glycosylation in the two host cell lines [31,32]. In accordance with Vestrheim et al, 2013, a lower sialic acid content was observed in HEK-derived immunoglobulins [33]. This is highly relevant when it comes to therapeutic usage, as sialic acid-rich proteins exhibit an extended half-life compared to non-sialylated proteins [34].…”
Section: Discussionmentioning
confidence: 58%
“…Whether this was due to individual differences or the actual vaccine formulation is uncertain, but the difference was not observed when the same volunteers received other vaccines. We have previously studied recombinant chimeric mouse‐human IgG3, which we found to contain more non‐fucosylated glycoforms compared to IgG1 . Interestingly, IgG3 antibodies in general appear superior to IgG1 regarding capacity for both ADCC and opsonophagocytic activity .…”
Section: Discussionmentioning
confidence: 91%
“…Terminal sialylation was detected at low amounts of under 5% on IgG derived from human plasma, CHO-K1, J558L and HEK293 cells [105,106,[108][109][110]112,113]. Due to low abundance, sialylated glycoforms of CHO-derived IgG was not clearly distinguishable through HPLC chromatograms and was thus not depicted during the two studies that utilized only liquid chromatography for glycan profiling [108,110].…”
Section: Immunoglobulin G (Igg)mentioning
confidence: 99%
“…Figure 2. Proposed structures of major N-linked glycans on IgG produced using mammalian cells [105][106][107][108][109][110][111][112][113][114]. Relative abundance of glycostructures, when determined by studies, is shown as percentage values.…”
Section: Coagulation Factor VII (Fvii)mentioning
confidence: 99%